Prognostic Role of Inflammatory and Nutritional Indices in NSCLC Patients Treated with Immune Checkpoint Inhibitors: Retrospective, Multicenter, Turkish Oncology Group Study of Overall and Elderly Populations - Ozkan Alan; Tugba Akın Telli; Sinem Akbas; Selver Isik; Eyyüb Çavdar; Kubilay Karaboyun; Aysegül Merc Cetinkaya; Ferhat Ekinci; Atike Pınar Erdoğan; Mahmut Büyükşimsek; Muhammed Muhittin Er; Melek Karakurt Eryilmaz; et al. (Medicina)
Background and Objectives: Despite advances in immunotherapy, predicting survival outcomes in patients with non-small-cell lung cancer (NSCLC) remains challenging. Inflammatory and nutritional indices such as the Prognostic Nutritional Index (PNI), Geriatric Nutritional Risk Index (GNRI), Neutrophil-to-Lymphocyte Ratio (NLR), Platelet-to-Lymphocyte Ratio (PLR), and Inflammatory Burden Index (IBI) have emerged as promising prognostic markers associated with overall survival (OS) in NSCLC patients. Materials and Methods: We retrospectively analyzed a total of 196 NSCLC patients treated with second-line nivolumab across multiple centers in Turkey. Of these, 101 patients aged ≥ 65 years were included in the elderly subgroup analysis. PNI, GNRI (in patients aged ≥ 65), and inflammation-based indices were calculated using pre-treatment laboratory values. ROC analysis determined optimal cut-off values. The Kaplan–Meier method and Cox proportional hazards models were used for survival analysis. Results: Median overall survival (OS) was 12.9 months in the full cohort and 12.1 months in patients aged ≥ 65. In univariate analysis, ECOG performance status (0–1), lower NLR (<3.3), lower PLR (<196.8), higher PNI (≥45.2), and higher GNRI (≥98.0) were significantly associated with longer OS. However, in the multivariate analysis adjusted for ECOG PS, NLR, PLR, and GNRI, only PNI remained an independent prognostic factor for OS in both the overall cohort [HR: 0.49, 95% CI: 0.26–0.92; p = 0.02] and elderly patients [HR: 0.45, 95% CI: 0.24–0.84; p = 0.01]. PNI is an independent prognostic biomarker for OS in NSCLC patients treated with immune checkpoint inhibitors. Conclusions: These findings support incorporating simple, cost-effective nutritional indices into clinical decision-making, particularly in elderly patients with NSCLC.